Cutaneous Syncytial Myoepithelioma Is Characterized by Recurrent EWSR1-PBX3 Fusions. (October 2019) - Jo, Vickie Y.; Antonescu, Cristina R.; Dickson, Brendan C.; Swanson, David; Zhang, Lei; Fletcher, Christopher D.M.; Demicco, Elizabeth G.
Abstract : Cutaneous syncytial myoepithelioma (CSM) is a rare but distinctive benign variant in the family of myoepithelial neoplasms of skin and soft tissue. CSM has unique morphologic and immunohistochemical features, characterized by intradermal syncytial growth of spindled, ovoid, and histiocytoid cells and consistent staining for S-100 protein and EMA, and differs from other myoepithelial tumors by showing only infrequent keratin staining. Rearrangement of the EWSR1 gene is now known to occur in up to half of all skin and soft tissue myoepithelial tumors, with a wide family of documented fusion partners. In 2013, we reported frequent (80%) EWSR1 rearrangements in CSM, but were unable to identify the fusion partner using available studies at that time. After recent identification of an index case of CSM harboring an EWSR1-PBX3 fusion, we used a combination of targeted RNA sequencing and fluorescence in situ hybridization (FISH) studies to investigate the genetic features of a cohort of CSM. An EWSR1-PBX3 fusion was identified in all 13 cases successfully tested. RNA sequencing was successful in 8/13 cases, all of which were found to have identical breakpoints fusing exon 8 of EWSR1 to exon 5 of PBX3 . FISH confirmed both EWSR1 and PBX3 rearrangements in 9/9 cases tested, which included 4 confirmed to have EWSR1-PBX3 fusion by RNA-Seq, 3 cases that failed RNA-Seq, and 2 cases examined by FISH alone. Two cases failed RNA sequencing but had no additional tissue remaining for FISH studies. Our findings demonstrate that EWSR1-PBX3 fusions occur in most (and possibly all) cases of CSM.